Ho Chi Minh's thought on human qualities and development strategy: Content and value - Diem , Vu Kim; Huong, Tran Nho; Chi, Pham Linh (Kajian Pendidikan, Seni, Budaya, Sosial dan Lingkungan, 2025)
The Vietnamese people represent the essence of Vietnamese culture, embodying unique characteristics that reflect both strengths and limitations. These qualities have been preserved and passed down through generations, shaping a distinct national identity. In the contemporary period of national renewal and integration, there is an urgent need to develop Vietnamese culture and human resources in line with the goals of sustainable development, while maintaining core cultural values. The objective of this study is to examine and highlight Ho Chi Minh’s perspectives on human development, especially the moral and ideological qualities that he believed essential for national progress. It further explores how these ideas can be integrated into current strategies for cultural and human development in Vietnam. This research employs a qualitative method using document analysis. Primary and secondary sources, including Ho Chi Minh’s speeches, writings, and relevant scholarly literature, were reviewed to identify key themes and principles related to human development. The analysis reveals that Ho Chi Minh emphasized the role of humans as both the driving force and ultimate goal of national development. He advocated for the cultivation of ethics, education, labour discipline, patriotism, and international solidarity. These values remain highly relevant in the current globalized context, where Vietnam faces both opportunities and challenges in cultural preservation and modernization. In conclusion, applying Ho Chi Minh’s human development philosophy in contemporary Vietnam offers a strategic foundation for nurturing citizens who are morally grounded, intellectually capable, and culturally confident—fostering national progress while maintaining cultural identity.